Dynamic modeling of a reactive distillation column - Kien Chung, Bert Chin (2012)
This research focuses on white box modeling of the dynamics of a reactive distillation column,precisely,one that is used for the commercial production of MTBE (methyl-tert-butyl-ether)by the reaction between methanol and isobutylene.The motivation for this study is mainly the process complexity posed by simultaneous reaction and separation which complicates the design and control of the column.In this study,an equilibrium model of reactive distillation column is developed in MATLAB by putting together the MESH equations and other equations like Francis weir formula and reaction rate law.Subsequently,the developed model is validated by comparison of simulation results with industrial data.Finally,the dynamic behaviour of the system is studied by applying step changes to each of the input variables, one at a time. The model of reactive distillation column is successfully developed.It is also proven to be a good representation of the column in the industry because model predictions and plant data come to a good agreement.